Knowing Talent from an Early Age: Between Normative Awareness and Reflective Ignorance of Students - Taufikin Taufikin (Social Science Academic, 2023)
This research departs from a conceptual unease about the importance of recognizing talent early in the framework of Ki Hadjar Dewantara’s thought. In this study, ‘talent’ refers to students’ inherent aptitudes, abilities, or natural potentials that can be recognized and developed. In his view, a free human being is an individual who can understand their potential from a young age through a continuous process of growth into adulthood. However, the reality of education shows a gap between awareness of the importance of talent and the ability to recognize it concretely. Here, ‘normative awareness’ means students’ understanding of the general or accepted importance of knowing their abilities, while ‘reflective awareness’ refers to their personal, conscious recognition of their own talents. This study uses a descriptive, quantitative approach and a survey method, involving 78 second-semester students from three mathematics classes. The research instrument consists of 12 questions that measure perception and self-awareness related to talent. The research results show that all respondents (100%) stated the importance of knowing their talents from an early age, but all (100%) also admitted they did not know their talents for sure. These findings indicate a disjunction between normative awareness and reflective awareness within the students. Theoretically, this condition indicates a weak guidance process within the education system that has not yet helped students fully recognize their potential. This research provides important implications for the development of a more reflective, dialogical, and individual potential-exploration-oriented, student-centered education model